2015
DOI: 10.5303/jkas.2015.48.6.381
|View full text |Cite
|
Sign up to set email alerts
|

Compact Groups of Galaxies With Complete Spectroscopic Redshifts in the Local Universe

Abstract: Dynamical analysis of compact groups provides important tests of models of compact group formation and evolution. By compiling 2066 redshifts from FLWO/FAST, from the literature, and from SDSS DR12 in the fields of compact groups in McConnachie et al. (2009), we construct the largest sample of compact groups with complete spectroscopic redshifts in the redshift range 0.01 < z < 0.22. This large redshift sample shows that the interloper fraction in the McConnachie et al. ( 2009) compact group candidates is ∼ 42… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 66 publications
4
55
0
Order By: Relevance
“…We compiled 40 redshifts from the NASA/IPAC Extragalactic Database (NED) and one redshift from the 1.5 m telescope on Mt. Hopkins (Sohn et al 2015). Tyler et al (2013) previously conducted a redshift survey for A2029 using the MMT/ Hectospec with the 270 line mm −1 grating.…”
Section: Spectroscopymentioning
confidence: 99%
“…We compiled 40 redshifts from the NASA/IPAC Extragalactic Database (NED) and one redshift from the 1.5 m telescope on Mt. Hopkins (Sohn et al 2015). Tyler et al (2013) previously conducted a redshift survey for A2029 using the MMT/ Hectospec with the 270 line mm −1 grating.…”
Section: Spectroscopymentioning
confidence: 99%
“…1. S15:McConnachie et al (2009) derived the CG samples using Hickson criteria from the SDSS-DR6 photometric catalogue(Adelman-McCarthy et al 2008) in two ranges of magnitude limit and resulted in two data-sets, Catalogue A and B. Later,Sohn et al (2015) supplied redshifts from FLOW/FAST observations and the SDSS-DR12, using velocity filter to check the candidates of Catalogue A. The final filtered sample (S15, hereafter) Their FoF algorithm find the neighbour galaxies within a fixed projected distance and velocity difference.…”
mentioning
confidence: 99%
“…A recent catalogue of Sohn et al (2015) revealed that the completeness corrected abundance of CGs is constant within an order of magnitude for z < 0.2. This is unexpected if the estimated crossing times of CGs are very short (≈0.02 Hubble times, Barnes 1989) and the theoretical timescales E-mail: lenhartsuiker@gmail.com † E-mail: ploeckinger@strw.leidenuniv.nl for all CG members to spiral into the group center by dynamical friction are of order a few crossing times, as historically assumed (White & Rees 1978).…”
Section: Introductionmentioning
confidence: 99%
“…If a large fraction of CGs only appear to be compact in projection, while being far more extended in radial direction, their coalescence timescales would be much longer than those for a spherical CG. In CGs extracted from mock galaxy catalogues built on the outputs of semi-analytical models of galaxy formation run on the Millennium Simulation (Springel et al 2005), a cut on the line-of-sight velocity of 1000 km s −1 from the median line-of-sight velocity of the group members (as also in the sample of Sohn et al 2015) increases the fraction of real groups from 35-44 per cent to 59-76 per cent, depending on the applied semi-analytic model (compare CG classes "mpCG" and "mvCG" in table 5 of Díaz-Giménez & Mamon 2010).…”
Section: Introductionmentioning
confidence: 99%